Answer:
The answer is C
Explanation:
If you substitute every x value for 5, you know that every equation can have 5 as an answer but C.
A. 3x+2=4x-3
Isolate the x(s) and combine like terms
3x+2-2=4x-3-2
3x=4x-5
3x-4x=4x-4x-5
-x=-5
-x(-1)=-5(-1)
x=5
Therefore A is a solution
B. (x+2)(x-5)=0
Substitution--Substitute every x for a 5
(7)(0)=0
anything multiplied by 0 will be 0
B. Is a solution because it is true.
C. 4x+2=15
Isolating the x(s) and combine like terms
4x+2-2=15-2
4x=13
4x÷4=13÷4
x=3.25
C is not a solution because x should equal to 5 but in this equation x can only be equal to 3.25. C is wrong.
We know our answer so we don't have to keep solving the rest of the equations.
But I'll just do D
D. 3x-10=x
Isolate the x(s) and combine like terms
3x-x-10=x-x
2x-10=0
2x=10
2x÷2=10÷2
x=5
D is a solution.